Python GUI programming cookbook : develop beautiful and powerful GUIs using the Python programming language - Meier, Burkhard A. (Packt Publishing, 2017)
Master over 80 object-oriented recipes to create amazing GUIs in Python and revolutionize your applications todayAbout This BookUse object-oriented programming to develop amazing GUIs in PythonCreate a working GUI project as a central resource for developing your Python GUIsEasy-to-follow recipes to help you develop code using the latest released version of PythonWho This Book Is ForThis book is for intermediate Python programmers who wish to enhance their Python skills by writing powerful GUIs in Python. As Python is such a great and easy to learn language, this book is also ideal for any developer with experience of other languages and enthusiasm to expand their horizon.What You Will LearnCreate the GUI Form and add widgetsArrange the widgets using layout managersUse object-oriented programming to create GUIsCreate Matplotlib chartsUse threads and talking to networksTalk to a MySQL database via the GUIPerform unit-testing and internationalizing the GUIExtend the GUI with third-party graphical librariesGet to know the best practices to create GUIsIn DetailPython is a multi-domain, interpreted programming language. It is a widely used general-purpose, high-level programming language. It is often used as a scripting language because of its forgiving syntax and compatibility with a wide variety of different eco-systems. Python GUI Programming Cookbook follows a task-based approach to help you create beautiful and very effective GUIs with the least amount of code necessary.This book will guide you through the very basics of creating a fully functional GUI in Python with only a few lines of code. Each and every recipe adds more widgets to the GUIs we are creating. While the cookbook recipes all stand on their own, there is a common theme running through all of them. As our GUIs keep expanding, using more and more widgets, we start to talk to networks, databases, and graphical libraries that greatly enhance our GUI's functionality. This book is what you need to expand your knowledge on the subject of GUIs, and make sure you're not missing out in the long run.Style and approachThis programming cookbook consists of standalone recipes, and this approach makes it unique.. While each recipe explains a certain concept, throughout the book you'll build a more and more advanced GUI, recipe after recipe. In some of the advanced topics, we simply create a new GUI in order to explore these topics in depth.